Dapsone and schistocytes: Thrombotic microangiopathy or not? - Alexis Archambeaud; Cédric Aumont; Claire Pouplard; Marie-Sarah Agier; François Maillot; Jean-Michel Halimi; Adrien Bigot (PLoS ONE, 2026)
Introduction Dapsone is used in many infectious and immunological diseases. Dapsone may cause haemolysis, particularly in individuals with glucose-6-phosphate dehydrogenase (G6PD) deficiency. This hemolysis is described as oxidative and is usually not associated with the presence of schistocytes. Patients and methods We conducted a single-centre retrospective observational study at the University Hospital of Tours, France (2005–2021). Adult patients who received dapsone and had a blood smear performed during treatment or within 7 days of discontinuation were included. Data were extracted from electronic medical records. Patients were classified as schistocyte-positive (≥0.1%) or -negative. Descriptive statistics were used; no further analyses were performed due to small sample size. Results During the 2005−2021 period, 19 adult patients received dapsone in our institution. Amongst them, 10 (52.6%) had detectable schistocytes, ranging from 2 to 44/1000 erythrocytes (13 ± 14.2). Patients with schistocytosis exhibited more severe hemolytic anemia, with a larger decrease in hemoglobin (−2.7 ± 1.4 g/dL vs −1.6 ± 2.12 g/dL), higher methemoglobinemia (5.2% vs 1.9%), more frequent low haptoglobin levels (88.9% vs 60%), and elevated LDH levels (557 U/L [239–671] vs 273 U/L [208–507]) compared to patients without schistocytosis. Platelet counts were similar between the two groups. No organ failure was identified in the reviewed medical records. Schistocytosis regressed upon discontinuation of treatment after 3–18 days. Conclusion Dapsone appears to be associated with hemolytic anemia and the presence of schistocytes, suggesting mechanical intravascular haemolytic anaemia. Whether Dapsone-associated biological thrombotic microangiopathy can be associated with target organ damage requires further investigation.